Can the use of the internet improve fish farmers' financial performance? Evidence from Ghana. (March 2023) - Twumasi Ankrah, Martinson; Asante, Dennis; Wang, Pengcheng; Ntiamoah, Evans Brako; Jiang, Yuansheng
Abstract: This study's investigation is about how Internet usage affects the financial performance of Ghanaian fish producers. We used a sample size of 222 fish farmers after employing the multistage sampling approach and the endogenous treatment regression (ETR) technique to achieve the study's objective. The results estimated after dealing with the endogeneity issue depict that the association between farm financial performance and Internet utilization has both heterogenous and homogenous impacts. Specifically, Internet use homogenously caused a significant rise in Net returns, Return on Investment (ROI), and Profit Margin of the fish farmers. Also, regarding the heterogeneous farm financial performance effect of using the Internet analysis, it was revealed that Internet use enhances the farmers' Net returns, ROI, and Profit Margin regardless of their gender or household income status. Generally, our findings recommend that policies that boost aquaculture practitioners' economic and financial performance should consider enhancing Internet connectivity across the nation. Highlights: Internet use has positive effects on fish farmers' financial Performance. Household income is a significant variable impacting fish farmers' financial Performance. Policymakers can help aquaculture development in the country.